Isolation and Characterization of Novel Lytic Bacteriophages Infecting Epidemic Carbapenem-Resistant Klebsiella pneumoniae Strains - Li, Min; Guo, Min; Chen, Long; Zhu, Chaowang; Xiao, Yuyi; Li, Pei; Guo, Hongxiong; Chen, Liang; Zhang, Wei; Du, Hong (Frontiers in Microbiology, 2020)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a significant clinical problem given the limited effective antibiotics. Alternative anti-bacterial agents, such as bacteriophages, can be used as a variety of valuable tool to treat the infections caused by these antibiotic-resistant bacteria. In this study, we isolated 54 phages from medical and domestic sewage wastewater between July and September 2019, and determined their host ranges against 54 clinical CRKP isolates collected from a tertiary hospital in Eastern China. These 54 CRKP isolates were from 7 sequence types (STs) and belonged to 9 capsular K locus types (KLs), harboring blaKPC-2 (n=49), blaNDM-1 (n=5), and blaIMP-4 (n=3). Among them, the epidemic KPC-2-producing ST11 strains were most predominant (88.9 %). The 54 phages showed different host ranges from 7 to 52 CRKP isolates, and lysis ability against some CRKP ST11 strains. The total host ranges of three phages can potentially cover all 54 CRKP isolates. Among the 54 phages, phage P545, classified as a member of Myoviridaes, order Caudovirales, had a relative wide host range (96.3%), a short latent period of 20 min, and a medium burst size of 82 PFU/cell and was stably maintained at different pH values (4-10) and temperatures (up to 60 oC). P545 showed the ability to inhibit biofilm formation and to degrade the formed mature biofilms. Taken together, our study showed the newly isolated phage P545 had relative wide host range, excellent properties and antibacterial activity as well as antibiofilm activity against clinical CRKP isolates, especially the epidemic CRKP ST11 strains, providing promising candidates for future phage therapy applications.